SIMULATION ANALYSIS OF ERGONOMIC DESIGN OF ELECTRIC MOTORBIKE FRAMES FOR RESIDENTIAL COMMUNITIES - Dwiky Ibrahim Kiki; Rizal Hanifi (Universitas Muhammadiyah Semarang, 2022)
Electric motorbikes are an economical and environmentally friendly means of transportation but have limitations on cruising and speed. In its development began to be used motorcycles with gasoline fuel. On the one hand, it is able to overcome the limitations of cruising power and speed, but on the other hand, it causes air pollution. To overcome this comes the technology of electric motorbikes. This electric bike does not cause air pollution because there is no combustion that occurs, has only an alight drawback which is limited electrical power and the length of time for recharger. In motor vehicles, the frame is the most important part that will hold and as a seat of various components, and support a load of these components on the vehicle system. Calculation of skeletal strength is very important to ensure the frame is able to withstand the load. Calculation of frame strength can be done manually (hand calculation) or by using Finite Element Analysis (FEA). on this frame, strength calculation using finite element analysis (FEA) with Solidworks software 2018. By using simulation can be known the value of von mises, displacement, and safety factors. from the results of the analysis of the smallest safety factor rider weight, 170 kg = 2.58. The results of the analysis of the construction of electric motorcycle frames carried out on static loading are safe because it is less than the minimum value of the safety factor of 1.25